The Guardians : a novel - Grisham, John; Beck, Michael, 1949- (New York, New York : Random House Audio, 2019)
Cullen Post, an Episcopal minister and lawyer, fights to exonerate Quincy Miller, who has spent over twenty years in prison for killing a lawyer, only to discover that powerful forces want the murder to remain unsolved.
Title from container.
Read by Michael Beck.
Keywords: False imprisonment -- Fiction; Murder -- Investigation -- Fiction; Suspense fiction; Audiobooks; Legal fiction